Characterization of muscle oxygenation response in well-trained handcyclists - Furno Puglia, V.; Paquette, M.; Bergdahl, A. (European Journal of Applied Physiology, 2024)
Purpose Peripheral responses might be important in handcycling, given the involvement of small muscles compared to other exercise modalities. Therefore, the goal of this study was to compare changes in muscle oxygen saturation (DELTASmO2) and deoxyhemoglobin level (DELTA[HHb]) between different efforts and muscles.